THE IMPORTANCE OF FOLK GAMES AND NATIONAL COMPETITIONS AS AN IMPORTANT FACTOR OF EDUCATION OF STUDENTS AND YOUTH (Scientific journal of the Fergana State University, 2024)
This article describes the analysis of traditional folk games and national competitions as an integral part of folk culture and art in human life, as well as the study of their importance and tasks as an important factor in educating students.